Habitual coffee consumption and genetic predisposition to obesity: gene-diet interaction analyses in three US prospective studies - T. Wang; Huang, T.; Kang, J. H.; Zheng, Y.; Jensen, M. K.; Wiggs, J. L.; Pasquale, L. R.; Fuchs, C. S.; Campos, H.; Rimm, E. B.; Willett, W. C.; Hu, F. B.; et al. (BMC MedBMC MedBMC Med, 2017)
BACKGROUND: Whether habitual coffee consumption interacts with the genetic predisposition to obesity in relation to body mass index (BMI) and obesity is unknown. METHODS: We analyzed the interactions between genetic predisposition and habitual coffee consumption in relation to BMI and obesity risk in 5116 men from the Health Professionals Follow-up Study (HPFS), in 9841 women from the Nurses' Health Study (NHS), and in 5648 women from the Women's Health Initiative (WHI). The genetic risk score was calculated based on 77 BMI-associated loci. Coffee consumption was examined prospectively in relation to BMI. RESULTS: The genetic association with BMI was attenuated among participants with higher consumption of coffee than among those with lower consumption in the HPFS (P interaction = 0.023) and NHS (P interaction = 0.039); similar results were replicated in the WHI (P interaction = 0.044). In the combined data of all cohorts, differences in BMI per increment of 10-risk allele were 1.38 (standard error (SE), 0.28), 1.02 (SE, 0.10), and 0.95 (SE, 0.12) kg/m(2) for coffee consumption of < 1, 1-3 and > 3 cup(s)/day, respectively (P interaction < 0.001). Such interaction was partly due to slightly higher BMI with higher coffee consumption among participants at lower genetic risk and slightly lower BMI with higher coffee consumption among those at higher genetic risk. Each increment of 10-risk allele was associated with 78% (95% confidence interval (CI), 59-99%), 48% (95% CI, 36-62%), and 43% (95% CI, 28-59%) increased risk for obesity across these subgroups of coffee consumption (P interaction = 0.008). From another perspective, differences in BMI per increment of 1 cup/day coffee consumption were 0.02 (SE, 0.09), -0.02 (SE, 0.04), and -0.14 (SE, 0.04) kg/m(2) across tertiles of the genetic risk score. CONCLUSIONS: Higher coffee consumption might attenuate the genetic associations with BMI and obesity risk, and individuals with greater genetic predisposition to obesity appeared to have lower BMI associated with higher coffee consumption.
Keywords: *Coffee; *Genetic Predisposition to Disease; Body Mass Index; Cohort Studies; Diet; Female; Follow-Up Studies; Humans; Male; Middle Aged; Obesity/*genetics/prevention & control; Prospective Studies; Risk Factors